2023
DOI: 10.1101/2023.09.05.556422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TGF-β blockade drives a transitional effector phenotype in T cells reversing SIV latency and decreasing SIV reservoirsin vivo

Jinhee Kim,
Deepanwita Bose,
Mariluz Araínga
et al.

Abstract: HIV-1 persistence during ART is due to the establishment of long-lived viral reservoirs in resting immune cells. Using an NHP model of barcoded SIVmac239 intravenous infection and therapeutic dosing of the anti-TGFBR1 inhibitor galunisertib (LY2157299), we confirmed the latency reversal properties of in vivo TGF-β blockade, decreased viral reservoirs and stimulated immune responses. Eight SIV-infected macaques on suppressive ART were treated with 4 2-week cycles of galunisertib. ART was discontinued 3 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Consequently, TGF-β inhibition was proposed as a strategy to target the latent reservoir. This has been demonstrated by recent studies that reported increased latency reversal in SIV-infected rhesus macaques by the TGF-β inhibitor galunisertib [293] and a decrease in the viral reservoir size, evidenced by reduced cell-associated viral DNA levels and likely resulting from the stimulation of SIV-specific immune responses [294].…”
Section: Kill Agentsmentioning
confidence: 76%
“…Consequently, TGF-β inhibition was proposed as a strategy to target the latent reservoir. This has been demonstrated by recent studies that reported increased latency reversal in SIV-infected rhesus macaques by the TGF-β inhibitor galunisertib [293] and a decrease in the viral reservoir size, evidenced by reduced cell-associated viral DNA levels and likely resulting from the stimulation of SIV-specific immune responses [294].…”
Section: Kill Agentsmentioning
confidence: 76%